The Benefits of Corporate Social Responsibility for Increasing Service Performances at X Hospital - I Gusti Ngurah Made Bayuningrat (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
The Hospital in conducting its business accountable to employees, customers, and communities, as well as the surrounding environment through the implementation of corporate social responsibility (CSR). The harmonious relationship between the company and the society in CSR. However, no studies link the effect of CSR on hospital service performance. The gap between social functioning capacity on the performance of hospitals, changes in the colonial mindset of purely social functions into the socio-economic, and more paradigms will give more and more receptive. The social activities that are considered capable of adding value, image enhancement, and performance of hospital services through the promotion of soft strategy, so are deemed necessary to study the effect of the implementation of CSR on hospital service performance. The goal is to determine whether there is an influence of CSR implementation on the performance of hospital services and whether it is useful for science as well as one of the efforts to improve the performance of hospital services towards adding value to the hospital so effective and efficient service which is one indicator of the success of hospital services can be realized. To determine whether the implementation of CSR effect hospital service performance (BOR, ALOS, TOI, BTO). The research was carried out in Kasih Ibu Hospital Tabanan. Samples were collected with a Likert scale questionnaire that has been validated and secondary data based on hospital reports. Implementation of CSR has a positive effect on the performance of hospital services.